The Relationship Between Insomnia and Tension-Type Headache Among Engineering Students at Universitas Nusa Cendana - Nainiti, Christov Dominick; Wungouw, Herman Pieter Louis; Ratu, Kristian; Hutasoit, Regina Marvina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Tension-Type Headache (TTH) is the most common headache and is often stress-related. Engineering students face high academic burdens that may trigger insomnia and affect pain thresholds. Despite neuroanatomical links between sleep and pain, evidence regarding the insomnia-TTH relationship in this group remains inconsistent. Objective: To determine the relationship between insomnia and TTH among engineering students at the Faculty of Science and Engineering, Universitas Nusa Cendana. This analytic observational study used a cross-sectional design. Stratified random sampling selected 52 active students from the cohorts of 2022, 2023, and 2024. Instruments included the Headache Screening Questionnaire (HSQ) and Insomnia Severity Index (ISI). Data were analyzed using the Spearman correlation test. The prevalence of insomnia among respondents was predominantly categorized as subthreshold insomnia (42.3%) and moderate clinical insomnia (42.3%). The prevalence of TTH was also high, with 65.4% of respondents experiencing TTH and 23.1% experiencing probable TTH. Bivariate analysis results indicated no significant relationship between insomnia and Tension-Type Headache (p=0.667; r= -0.061). The very weak negative correlation indicates that an increase in insomnia scores was not statistically associated with an increase in TTH incidence. Insomnia and TTH prevalence are high among engineering students, but no significant relationship was found between insomnia and TTH in this population.